A Qualitative Study on the Establishment of an Interpersonal Violence Registry System in Iran - Iezadi, Shabnam (Journal of interpersonal violence, 2022)
Establishment of an interpersonal-violence registry system (IPVRS) is a promising initiative to tackle violence. This qualitative study aimed to fill the gap in knowledge regarding the feasibility of establishing the IPVRS in the East-Azerbaijan province of Iran. This qualitative study using content analysis was conducted to explore the importance, challenges, and facilitating factors of establishing the IPVRS from the viewpoints of stakeholders. Forty-six individuals from the Forensic Medical Organization, the University, the Welfare Organization, the Training and Education Organization, hospitals, and primary health centers participated in the study. Six themes and 13 sub-themes were identified. The importance of the establishment of the IPVRS was sub-categorized into two main themes, including violence as a public health priority and severe consequences of violence including intensive health and social outcomes and high use of medical services. The most critical challenges of establishing the IPVRS were categorized into two main themes including victims? under-reporting due to financial difficulties as well as psychosocial barriers and structural barriers such as organizational barriers and methodological challenges. Inter-sectoral partnership was identified as the main facilitating factor in the successful establishment of the IPVRS. The participants recommended improving the development of the IPVRS by stepwise development of the program, resource absorption from other beneficiary organizations, and making more coverage in the registry system. In conclusion, the establishment of the IPVRS is identified as an effective strategy to tackle violence-related issues. Close collaboration with different governmental and non-governmental sectors and the gradual development of the registry system can pave the way for establishing the IPVRS. This study has several implications for identifying potential challenges and facilitators of the IPVRS applicable to other developing countries with similar contexts.